The tale of the duck and the fishes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Here are two simple, ingenious examples of the art, an ancient art in the Far East, of the rational use of natural resources, and, as it were, of killing two birds with one stone, or more to the point, raising gamebirds alongside fish. In the first...